2011
DOI: 10.3109/0886022x.2011.560401
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Is Related with Uremic Pruritus in Diabetic and Nondiabetic Hemodialysis Patients

Abstract: Objective: Uremic pruritus (UP) remains a frequent problem in hemodialysis (HD) patients and is related to mortality. Poor glycemic control, as evaluated by hemoglobin A1c (HbA1c), is also associated with morbidity and mortality in HD patients. In this study, we investigated the relationship between UP and HbA1c in HD patients. Methods: Sociodemographic, clinical, and laboratory variables, depressive symptoms, and health-related quality of life were assessed. Severity of UP was evaluated by visual analogue sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 39 publications
3
20
0
1
Order By: Relevance
“…According to the other reports, pruritus may be independently associated with higher calcium [18,20,35], phosphorus, and iPTH concentrations [40]. We showed that higher Ca × P product significantly increased the risk of itching on dialysis (Table 5).…”
Section: Discussionsupporting
confidence: 64%
“…According to the other reports, pruritus may be independently associated with higher calcium [18,20,35], phosphorus, and iPTH concentrations [40]. We showed that higher Ca × P product significantly increased the risk of itching on dialysis (Table 5).…”
Section: Discussionsupporting
confidence: 64%
“…The present study also found that DMN patients with HD had physical problems related to the eyes, blood pressure, cardiovascular disease, skin, and nails, and problems in everyday life such as shopping, mobility, dressing oneself, and job; these were not statistically observed among DMN patients without HD. Indeed, these HD-associated physical symptoms [23,24] and social activities and participation [4] were previously reported in individual studies. In short, these physical and social problems might be invisible to health professionals unless they deliberately ask their patients about possible problems they might be experiencing.…”
Section: Discussionmentioning
confidence: 92%
“…Multiple comorbidities have been associated with an increased risk of severe itch, including concurrent cardiovascular disease, congestive cardiac failure, lung disease, liver disease and neurological disease [ 3 , 16 ]. Diabetes mellitus is also reported to be associated with worse itch, with poor glycaemic control and a higherhaemoglobin A1c correlating with greater symptom burden [ 29 ]. However, the converse was seen in the GEHIS study, with a lower prevalence of itch in diabetic patients [ 28 ].…”
Section: Potential Risk Factors For Ckd-ap In Dialysis Patientsmentioning
confidence: 99%